2017
DOI: 10.1186/s13073-017-0487-0
|View full text |Cite
|
Sign up to set email alerts
|

Whole-exome sequencing in amyotrophic lateral sclerosis suggests NEK1 is a risk gene in Chinese

Abstract: BackgroundAmyotrophic lateral sclerosis (ALS) is a progressive neurological disease characterised by the degeneration of motor neurons, which are responsible for voluntary movement. There remains limited understanding of disease aetiology, with median survival of ALS of three years and no effective treatment. Identifying genes that contribute to ALS susceptibility is an important step towards understanding aetiology. The vast majority of published human genetic studies, including for ALS, have used samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 45 publications
1
16
0
1
Order By: Relevance
“…Afterwards, it was identified that a significant association of rs10463311 spanning GPX3-TNIP1 with ALS in the meta analysis of GWAS data from Chinese and European cohorts (Benyamin et al, 2017). Recently, NEK1 was reported a risk ALS gene based on the meta-analysis of WES data from large cohorts of Chinese and European ancestry (Gratten et al, 2017), which was consistent with the two studies from several European countries (Brenner et al, 2016; Kenna et al, 2016) and considered the first study to define a new gene with WES data in Chinese ALS.…”
Section: Genetic Characteristics Of Chinese Als Patientssupporting
confidence: 64%
“…Afterwards, it was identified that a significant association of rs10463311 spanning GPX3-TNIP1 with ALS in the meta analysis of GWAS data from Chinese and European cohorts (Benyamin et al, 2017). Recently, NEK1 was reported a risk ALS gene based on the meta-analysis of WES data from large cohorts of Chinese and European ancestry (Gratten et al, 2017), which was consistent with the two studies from several European countries (Brenner et al, 2016; Kenna et al, 2016) and considered the first study to define a new gene with WES data in Chinese ALS.…”
Section: Genetic Characteristics Of Chinese Als Patientssupporting
confidence: 64%
“…In a rare variant burden (RVB) analysis of a whole-exome from index FALS cases, a higher mutation profile of NEK1 was found in FALS and SALS cases [41]. Similarly, in a sample of Chinese patients, whole-exome analysis contributed to European evidence showing that NEK1 is an ALS gene as well as reporting new variants [43]. Furthermore, given the few studies endorsing NEK1 as an ALS gene and the ethnic heterogeneity of genes from ALS patients, Shu et al [44] published a mutation screening of NEK1 from Chinese ALS patients by Polymerase Chain Reaction (PCR)-sanger sequencing, which led to the identification of coherent data of risk variants of NEK1 and, in total, three novel heterozygous loss-of-function mutations were identified.…”
Section: Nek1mentioning
confidence: 92%
“…Among the new genes, the FTO genomic variants are founder mutations for the Greek population (Mitropoulos, Katsila, Patrinos, & Pampalakis, 2018). NEK1 pathogenic variants constitute a risk factor in the Chinese population (Gratten et al, 2017). This knowledge may be applied in the designing of new genetic testing based on the population under study.…”
Section: Genomic Biomarkers: Identifying the Genetic Basis Of Alsmentioning
confidence: 99%